2012
DOI: 10.1186/1471-2334-12-94
|View full text |Cite
|
Sign up to set email alerts
|

The risk of AIDS-defining events is decreasing over time in the German HIV-1 Seroconverter Cohort

Abstract: BackgroundWith ageing of the HIV-infected population, long-term exposure to treatment, varying adherence, emerging resistance and complications to therapies, effectiveness of Highly Active Antiretroviral Therapy (HAART) needs to be monitored continuously at the population level. The German HIV-1 Seroconverter Cohort is a multi-centre, open, long-term observational cohort including patients with a known or reliably estimated date of HIV-infection i.e. last negative and first positive HIV antibody test within a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
2
3
0
Order By: Relevance
“…Our main findings with regard to the IRs are consistent with other studies in the Western European and North American context, which showed that the rates of AIDS‐defining opportunistic infections among people living with HIV have continuously declined since the advent of effective ART [23–25]. As we observed this decline over the course of both follow‐up and calendar periods, our findings also build on existing evidence that the decreasing rates can be attributed to both consistent clinical supervision and improved ART regimens, together with adapted guidelines recommending earlier treatment [26–29].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our main findings with regard to the IRs are consistent with other studies in the Western European and North American context, which showed that the rates of AIDS‐defining opportunistic infections among people living with HIV have continuously declined since the advent of effective ART [23–25]. As we observed this decline over the course of both follow‐up and calendar periods, our findings also build on existing evidence that the decreasing rates can be attributed to both consistent clinical supervision and improved ART regimens, together with adapted guidelines recommending earlier treatment [26–29].…”
Section: Discussionsupporting
confidence: 90%
“…When comparing IRs between transmission groups, our analyses of the unadjusted rates showed that PWID had a slower and less pronounced decline over the entire course of clinical care, and PHPC who enrolled in the latest calendar period had substantially higher rates during their first years than those in the other groups. The higher rates among PWID could be related to poorer therapy access and adherence as well as generally worse health conditions among people in this group, which has also been reported by previous studies [29–32]. Similarly, it was found that PHPC are more often diagnosed in advanced stages and also present with higher rates of comorbid illnesses [33, 34], potentially resulting from obstacles such as limited access to healthcare and socioeconomic challenges, rendering PHPC more vulnerable to disease progression [35].…”
Section: Discussionsupporting
confidence: 56%
“…For the current analysis, data of patients enrolled in the cohort from January 2001 (introduction of the co-formulation boosted protease inhibitors Lopinavir/Ritonavir in Germany [ 18 ]) through December 2011 were extracted from the central ClinSurv HIV database. Basic demographic characteristics including age, gender and geographic origin are recorded as time-fixed covariates at the time of enrollment.…”
Section: Methodsmentioning
confidence: 99%
“…The current standard of care for HIV infection is highly active antiretroviral therapy (HAART), a treatment strategy that uses cocktails of antiretroviral drugs to control HIV replication and to delay disease progression to AIDS. HAART has greatly improved outcomes for individuals living with HIV [2,3]. It efficiently inhibits viral replication and is highly effective at suppressing viral loads.…”
Section: Hiv and Haart: Limitations Of The Current Standard Of Carementioning
confidence: 99%